Effects of sources, transport, and postdepositional processes on levoglucosan records in southeastern Tibetan glaciers. Issue 14 (22nd July 2016) - You, Chao; Yao, Tandong; Xu, Baiqing; Xu, Chao; Zhao, Huabiao; Song, Lili
Abstract: Tibetan glaciers are substantially influenced by smoke aerosols derived from intensive biomass burning (BB) emissions in surrounding regions. However, knowledge regarding the impact of smoke aerosols on Tibetan glaciers is limited. Here we present levoglucosan records extracted from two southeastern Tibetan (SET) glaciers. We found that Zuoqiupu (ZQP) Glacier, situated on the windward side of the mountains, is more strongly affected by BB aerosols when compared with Cuopugou (CPG) Glacier on the leeward side. On ZQP Glacier, the highest levoglucosan concentration was detected at an elevation near the equilibrium line altitude. The injection height of smoke plumes and the actions of postdepositional processes on the glacier surface determined the distribution patterns of levoglucosan concentrations at different altitudes. Spatiotemporal variability in levoglucosan and black carbon distributions after deposition may be caused by the different source characteristics and by different postdepositional geochemical behaviors on the glacier surface. Intense wildfires can lead to extremely high concentrations (higher than 25 ng mL −1 ) of black carbon in ice near the surface of SET glaciers and can therefore play an important role in glacial melt during the premonsoon season. Key Points: Levoglucosan evidence for smoke aerosols affecting Tibetan glaciers Spatiotemporal variations of levoglucosan on southeastern Tibetan glaciers Biomass burning can lead to high BC on glaciers and facilitate for glacier melting